2020
DOI: 10.1186/s12954-020-00357-4
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to HIV risks among young people who use drugs (YPUD) in three cities in Vietnam: time to develop targeted interventions

Abstract: Introduction: The aim of this study is to identify the profiles of young people who use drugs (YPUD) and their exposure to HIV risks in the 3 main cities of Vietnam, Haiphong, Hanoi, and Ho Chi Minh City (HCMC), in order to design a community-based intervention to prevent HIV. Methods: A survey using respondent-driven sampling (RDS) was conducted among YPUD aged 16-24. Participants were eligible if they reported drug use, confirmed by a urine test. After obtaining informed consent, they were screened for HIV/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The city of Hai Phong started to develop peer-supported interventions many years ago with the involvement of the city health authorities, national NGOs and international agencies, targeting key and hard-to-reach populations. 33,51 It clearly participated in the success of the intervention presented here and this raises the question of the reproducibility of this type of mobilization of actors in other provinces. Cost and cost-effectiveness of the intervention need to be compared with the classic model of care to develop advocacy toward health authorities.…”
Section: Discussionmentioning
confidence: 80%
“…The city of Hai Phong started to develop peer-supported interventions many years ago with the involvement of the city health authorities, national NGOs and international agencies, targeting key and hard-to-reach populations. 33,51 It clearly participated in the success of the intervention presented here and this raises the question of the reproducibility of this type of mobilization of actors in other provinces. Cost and cost-effectiveness of the intervention need to be compared with the classic model of care to develop advocacy toward health authorities.…”
Section: Discussionmentioning
confidence: 80%
“…Considering only moderate to severe depression, a recent meta‐analysis focusing on PWID showed a pooled prevalence of 59.7% [95]. Similarly, a recent survey conducted among young people who used drugs in Vietnam showed that criteria for moderate to severe depression were found in 50% of the subjects [98]. These data therefore suggest that the proportion of people who need to be referred to a psychiatrist would be higher in the target population and positive predictive value will be greater.…”
Section: Discussionmentioning
confidence: 99%
“…[11] In Vietnam HIV prevalence was 6.3% among young people (15-24 years) predominantly using methamphetamines and higher (15%) among those with a history of injecting. [12] In Myanmar, people using methamphetamines in Shan State frequently reported inconsistent condom use and multiple sex partners pointing to the potential for sexual transmission of HIV. [7]…”
Section: Introductionmentioning
confidence: 99%
“…[11] In Vietnam HIV prevalence was 6.3% among young people (15-24 years) predominantly using methamphetamines and higher (15%) among those with a history of injecting. [12] In Myanmar, people using methamphetamines in Shan State frequently reported inconsistent condom use and multiple sex partners pointing to the potential for sexual transmission of HIV . [7] There is a growing body of evidence documenting high HIV prevalence (34.9%) among PWID in Myanmar ranging from 7.6% to 61% and higher in rural areas of Bhamo and Waingmaw (61-56%) in Kachin State.…”
Section: Introductionmentioning
confidence: 99%